Effects of disposable pull-through brush types for reprocessing of flexible endoscopes in clinical environment - Remus O. Anders; Adriana M. Airo; Eve Capistran; Anita Chin; Garry Bassi; Tony Mazzulli (Infection Prevention in Practice)
Summary: Evaluating the effectiveness of different brush types used during the cleaning and reprocessing of flexible endoscopes is challenging. This study compared the yield of microbial growth from endoscopes that had been used clinically before and after cleaning with different brush types (bristle, squeegee, and hybrid). Endoscopes used to perform a total of 91 medical procedures on 82 patients were included. Quantitative bacterial cultures yielded no statistical differences between the different brushes used. Colonoscopes and gastroscopes surveyed after rigorous cleaning steps resulted in a drop in colony counts between pre- and post-cleaning from 1.45E+8 (±5.21E+07) to 2.5 (±0.13) individual colonies suggesting that the overall cleaning process was effective regardless of the brush type used.